Survey on the Updated German S3 Guideline for Intensive Care in Cardiac Surgery Patients - Zajonz, Thomas Simon; Habicher, Marit; Böning, Andreas; Heringlake, Matthias; Ender, Jörg; Markewitz, Andreas; Brenck, Florian; Sander, Michael (The Thoracic and Cardiovascular Surgeon, 2023)
Background The German guideline on intensive care treatment of cardiac surgical patients provides evidence-based recommendations on management and monitoring. It remains unclear if, respectively, to which degree the guidelines are implemented into the daily practice. Therefore, this study aims to characterize the implementation of guideline recommendations in German cardiac surgical intensive care units (ICUs).Methods An internet-based online survey (42 questions, 9 topics) was sent to 158 German head physicians of cardiac surgical ICUs. To compare the effect over time, most questions were based on a previously performed survey (2013) after introduction of the last guideline update in 2008.Results A total of n = 65 (41.1%) questionnaires were included. Monitoring changed to increased provision of available transesophageal echocardiography specialists in 86% (2013: 72.6%), SvO2 measurement in 93.8% (2013: 55.1%), and electroencephalography in 58.5% (2013: 2.6%). The use of hydroxyethyl starch declined (9.4% vs. 2013: 38.7%), gelatin 4% presented the most administered colloid with 23.4% (2013: 17.4%). Low cardiac output syndrome was primarily treated with levosimendan (30.8%) and epinephrine (23.1%), while norepinephrine (44.6%) and dobutamine (16.9%) represented the most favored drug combination. The main way of distribution was web-based (50.9%), with increasing impact on therapy regimens (36.9% vs. 2013: 24%).Conclusion Changes were found in all questioned sectors compared with the preceding survey, with persisting variability between ICUs. Recommendations of the updated guideline have increasingly entered clinical practice, with participants valuing the updated publication as clinically relevant.
Keywords: cardiac; intensive care; postoperative care; guidelines